Sesquiterpenoids from Dysoxylum amooroides Stem Bark: Isolation, Structure Determination, and Cytotoxicity Against MCF-7 Breast Cancer Cells - Gunawan, Latifah; Mustofa, Hidayat Nurul; Naini, Al Arofatus; Harneti, Desi; Hidayat, Ace Tatang; Nurlelasari, Nurlelasari; Maharani, Rani; Mayanti, Tri; Fajriah, Sofa; Awang, Khalijah; Azmi, Mohamad Nurul; Supratman, Unang (Indonesian Journal of Chemistry, 2025)
Three sesquiterpenoids, guaianediol (1), alismol (2), and spathulenol (3), were isolated from the n-hexane and ethyl acetate extracts of the stem bark of Dysoxylum amooroides. The three compounds were found in D. amooroides species for the first time. The structures of the isolated compounds were identified and established based on an extensive spectroscopic analysis involving HR-TOF-ESI-MS, IR, and NMR data, as well as a comparison with the previously reported works of literature. Compounds 1-3 were further assessed for cytotoxic effects against MCF-7 breast cancer cells. Guaianediol (1) showed inactive activity with IC50 > 100 µM, alismol (2) showed weak activity with IC50 value of 82.1 µM and spathulenol (3) showed considerable activity with an IC50 value of 15.2 µM. A brief structure-activity relationship and comparison with the previous works were also discussed to understand better the role of guaiane- and aromadendrane-type sesquiterpenoids in the biological activity perspective.